The Use of Information and Communications Technology to Foster the Competitiveness of the Entrepreneurial Organizations within the Education and Science Sector - A. Galushkin, Alexander (International Journal of Engineering and Technology, 2018)
In recent years, a new market trading in cryptocurrencies and instruments based on them has been formed. The market of this paper addresses the use of information and communications technology to optimize the operation of institutions of higher learning and scientific organizations, boost their competitiveness through the systematization of their business processes, and enhance their qualitative characteristics. The author looks into employing information and communications technology to organize the institution’s distance learning systems, electronic educational environment, and electronic (online) learning system. The paper emphasizes that the use of information systems is of particular convenience with regard to setting up electronic research and scholarly libraries, which could be accessed over the Internet from just about anywhere in the world regardless of their actual physical location. Along with practical aspects, the author also examines some of the issue’s regulatory foundations and some of the compliance practices related to it. The paper stresses that, in a climate when virtually any object is vulnerable to attack by intruders, of particular relevance is the issue of ensuring information security both domestically and globally. The author concludes by drawing a set of inferences that are both of a practical nature and of a theoretical one.